2017
DOI: 10.1021/acs.oprd.7b00192
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Characterization of an in Situ Wet Mill Operation

Abstract: The integration of an in situ wet mill and continuous mixed suspension mixed product removal crystallizer (MSMPR) is studied in this work for the cooling crystallization of paracetamol from an aqueous isopropanol mixture. The continuous operation was monitored using focused beam reflectance measurements (FBRM) to determine the onset of the steady state. The impact of various operational conditions of both continuous in situ mill and MSMPR unit is studied. The paper demonstrates that the operational conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…Such a reduction should be avoided in API production. In recent years, integrated wet-milling and crystallization technologies have been broadly developed to intensify the crystallization processes. , , Engstrom et al proposed a scaling approach for API particle-size reduction by introducing toothed rotor-stator wet milling based on cooling crystallization. Yang et al proposed an in situ seed-generator method by integrating the upstream application of high-shear rotor-stator wet milling with continuously mixed suspension mixed product removal crystallization (MSMPRC), significantly reducing the startup duration and enhancing the product yield.…”
Section: Progress and Problems In Seeding Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a reduction should be avoided in API production. In recent years, integrated wet-milling and crystallization technologies have been broadly developed to intensify the crystallization processes. , , Engstrom et al proposed a scaling approach for API particle-size reduction by introducing toothed rotor-stator wet milling based on cooling crystallization. Yang et al proposed an in situ seed-generator method by integrating the upstream application of high-shear rotor-stator wet milling with continuously mixed suspension mixed product removal crystallization (MSMPRC), significantly reducing the startup duration and enhancing the product yield.…”
Section: Progress and Problems In Seeding Techniquesmentioning
confidence: 99%
“…It is generally recommended that crystal seeds should be added at the lowest possible supersaturation, but a lower seeding supersaturation might lead to seed dissolution . Moreover, the supersaturation at the seeding time is also related to the seed mass, seed size and solution temperature; thus, a suitable supersaturation should enable a maintained level of seed growth without dissolution and secondary nucleation . However, it is not easy to identify a suitable seeding temperature because the temperature effects are commonly coupled with supersaturation, seed loading and the resulting temperature profile. , Nevertheless, some studies ,, have found that the seeding temperature is crucial for controlling the crystal form, shape, and even final product quality.…”
Section: Progress and Problems In Seeding Techniquesmentioning
confidence: 99%
“…In Eq. (20) denotes the mean size of the th cell, � | +1 is the number of daughter crystals of size L (corresponding to the th grid cell), born from the breakage of a crystal of size (corresponding to th grid). This simple equation, however, will require adjustment since it does not take into consideration the grid size (ℎ ).…”
Section: Finite Volume Solution Of the Model Equationsmentioning
confidence: 99%
“…Acevedo et al and Yang et al incorporated an in situ wet mill to a continuous mixed-suspension, mixed-product removal crystallizer. 21,27 Two different integration strategies were studied. When used downstream, milling was identified as a size reduction tool, whereas upstream milling served as a continuous seed generator with heterogeneous primary nucleation as the major kinetics inside.…”
Section: Introductionmentioning
confidence: 99%
“…Salvatori et al introduced a 3-stage process, repeating cycles among cooling crystallization, intermediate milling, and fines dissolution to tune crystal size and shape of different compounds. An experimental campaign was performed to understand the influence of wet mill speed, number of cycles, and mass dissolved during the heating stage. Acevedo et al and Yang et al incorporated an in situ wet mill to a continuous mixed-suspension, mixed-product removal crystallizer. , Two different integration strategies were studied. When used downstream, milling was identified as a size reduction tool, whereas upstream milling served as a continuous seed generator with heterogeneous primary nucleation as the major kinetics inside.…”
Section: Introductionmentioning
confidence: 99%